A New Tool for Digital Alignment in Virtual Anthropology. Issue 7 (22nd February 2019) - Profico, Antonio; Buzi, Costantino; Davis, Christopher; Melchionna, Marina; Veneziano, Alessio; Raia, Pasquale; Manzi, Giorgio
ABSTRACT: The study of the fossil record is fundamental to understand the evolution of traits. Because fossil remains are often fragmented and/or deformed by taphonomic processes, a preliminary realignment of their constituent parts is often necessary to properly interpret their shapes. In virtual anthropology, these procedures are carried out using digital models of the remains. We present a new semi‐automatic alignment R software, Digital Tool for Alignment (DTA), which uses the shape information contained in a reference sample to find the best alignment solution for the disarticulated regions. We tested DTA on three different case‐studies: (1) a sample of 14 primate species including both male and female individuals, (2) a simulated, disarticulated skull of Homo sapiens, and (3) a real disarticulated human fossil specimen, Amud 1 ( Homo neanderthalensis ). In the first case study, we simulated disarticulation directly on digital models of the primate skulls and tested alignment quality as a function of phylogenetic proximity, sex, and body size. In the second, we compared DTA to manual alignments conducted for the same digital models. Finally, we performed DTA on a real‐world case study. We found that phylogenetic proximity provides is the most important factor for alignment efficiency. However, sex and allometric effects might also be important and should therefore be taken into account at selecting reference models for alignments. DTA performs at least as well as manual alignments. Yet, as compared to manual procedures, it is faster, requires no prior anatomical knowledge and expertise and allows indefinite manipulation of the fossil items. Anat Rec, 302:1104–1115, 2019. © 2019 Wiley Periodicals, Inc.